Production of Substituted l-Tryptophans by Fermentation - Fukuda, D. S. (1971)
Claviceps purpurea has been shown to produce extracellular l-tryptophan from indole in stirred fermentors. The substrate specificity of this conversion was investigated by using substituted indoles, anthranilic acid, and 4-chloro-anthranilic acid. Addition of 2-, 4-, 5-, 6-, and 7-methyl indole or 6-chloroindole to C. purpurea C1M produced the corresponding substituted l-tryptophan. In contrast, addition of l-methyl, 6-trifluoromethyl, 6-nitro-, or 4-benzyloxy-substituted indoles, or anthranilic and 4-chloroanthranilic acids did not produce detectable amounts of the corresponding tryptophan.